Tissue- and Cell-Specific Cytokinin Activity in Populus × canescens Monitored by ARR5::GUS Reporter Lines in Summer and Winter - Paul, Shanty; Wildhagen, Henning; Janz, Dennis; Teichmann, Thomas; Hänsch, Robert; Polle, Andrea (Frontiers in Plant Science, 2016)
Cytokinins play an important role in vascular development. But knowledge on the cellular localization of this growth hormone in the stem and other organs of woody plants is lacking. The main focus of this study was to investigate the occurrence and cellular localization of active cytokinins in leaves, roots and along the stem of Populus × canescens and to find out how the pattern is changed between summer and winter. An ARR5::GUS reporter construct was used to monitor distribution of active cytokinins in different tissues of transgenic poplar lines. Three transgenic lines tested under outdoor conditions showed no influence of ARR5::GUS reporter construct on the growth performance compared with the wildtype, but one line lost the reporter activity. ARR5::GUS activity indicated changes in the tissue- and cell type-specific pattern of cytokinin activity during dormancy compared with the growth phase. ARR5::GUS activity, which was present in the root tips in the growth season, disappeared in the root tips in winter. In the stem apex ground tissue, ARR5::GUS activity was higher in winter than in summer. Immature leaves from tissue-culture grown plants showed inducible ARR5::GUS activity. Leaf primordia in summer showed ARR5::GUS activity, but not the expanded leaves of outdoor plants or leaf primordia in winter. In stem cross sections, the most prominent ARR5::GUS activity was detected in the cortex region and in the rays of bark in summer and in winter. In the cambial zone the ARR5::GUS activity was more pronounced in the dormant than in growth phase. The pith and the ray cells adjacent to the vessels also displayed ARR5::GUS activity. In silico analyses of the tissue-specific expression patterns of the whole PtRR type-A family of poplar showed that PtRR10, the closest ortholog to the Arabidopsis ARR5 gene, was usually the most highly expressed gene in all tissues. In conclusion, gene expression and tissue-localization indicate high activity of cytokinins not only in summer, but also in winter. The presence of the signal in meristematic tissues supports their role in meristem maintenance. The reporter lines will be useful to study the involvement of cytokinins in acclimation of poplar growth to stress.